Mobile botnet detection model based on retrospective pattern recognition - Eslahi M.; Yousefi M.; Naseri M.V.; Yussof Y.M.; Tahir N.M.; Hashim H. (Science and Engineering Research Support Society, 2023)
Complex networks; HTTP; Hypertext systems; Mobile security; Pattern recognition; Botnet detections; Botnets; BYOD; Command and control; Experimental test; Network-based modeling; Packet payloads; Traffic analysis; Malware